Rethinking Linkage To The West: What Authoritarian Stability In Singapore Tells Us - Su, Mei Ooi (Penerbit Universiti Sains Malaysia (USM Press), 2016)
Recent regime change literatures compellingly assert that linkage to the West has been a significant factor in democratisation where the organisational capacity of authoritarian incumbents has overwhelmingly weakened pro-democracy forces. Detailed case studies confirming these findings have not included Singapore although high levels of linkage to the West suggest that democratisation should have taken place there. This qualitative case study fills the empirical and theoretical gap by explaining why linkage has so far failed to raise the cost of authoritarianism for Singapore's government. By eschewing the current structural approach, which conceptualises linkage as mere channels of external pressure or influence, this analysis treats each dimension of linkage as arenas of political interaction where external democratising pressure or influence are generated, mediated or precluded. This agency-centred approach exposes the politics of linkage and thereby enables us to explain why linkage to the West does not always have the expected impact on regime change. These findings open up the research agenda of regime change studies by pointing the way forward for future studies of otherwise inexplicable cases where high linkage has not led to democratisation.